Force-monitoring ring based on white-light interferometry for bridge cable force monitoring and its temperature compensation. Issue 6 (April 2019) - Li, Shengyuan; Lv, Haifeng; Kuang, Yachuan; Deng, Nianchun; Sun, Changsen; Zhao, Xuefeng
This article proposes a novel white-light interference (WLI) force-monitoring ring for bridge cable force monitoring and temperature compensation. The WLI force-monitoring ring employs a sensing optical fiber wrapped around the outer surface of an elastomer to measure the expansion caused by applied load and temperature. By installing WLI force-monitoring ring between the anchor plate and the spherical plate of the cable, cable force can be captured by the sensing optical fiber and thus measured after temperature compensation. Based on white-light interferometry, two force-monitoring rings with resolution of 0.25 µ are designed. To find a route to temperature compensation, laboratory experiments are carried to study the effects of temperature on WLI force-monitoring ring both in free and forced states. Theoretical analysis and calibration experiments are implemented to verify the effectiveness of the proposed WLI force-testing ring, and the experiment results expose that the temperature-induced strain can be compensated using a WLI force-monitoring ring in free state. As a comparison, similar work is made for four fiber Bragg grating sensors attached to the elastomer evenly near the sensing optical fiber. The comparison results verify that the WLI method achieves better linear relation and repeatability than fiber Bragg grating. The WLI force-monitoring ring provides a high-precision and low-cost method for bridge cable force monitoring.